The lyrical testament of Daniel Devoto: "Oda en el Día de Santa Cecilia" - Rubio Jiménez, Jesús (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The last poetic composition of the philologist and musicologist Daniel Devoto can be read following two keys, two lines of force that culminate the investigative and creative career of this writer: the song of celebration of the music and the moving narration of his life, dedicated to his service.
Keywords: Daniel Devoto; Oda en el Día de Santa Cecilia; poetry; music